Hospital Readmissions in Patients with Cirrhosis: A Systematic Review - Orman, Eric S. (J Hosp Med, 2018)
BACKGROUND: Hospital readmission is a significant problem for patients with complex chronic illnesses such as liver cirrhosis. PURPOSE: We aimed to describe the range of readmission risk in patients with cirrhosis and the impact of the model for end-stage liver disease (MELD) score. DATA SOURCES: We conducted a systematic review of studies identified in Ovid MEDLINE, PubMed, EMBASE, CINAHL, the Cochrane Library, Scopus, Google Scholar, and ClinicalTrials.gov from 2000 to May 2017. STUDY SELECTION: We examined studies that reported early readmissions (up to 90 days) in patients with cirrhosis. Studies were excluded if they did not examine the association between readmission and at least 1 variable or intervention. DATA EXTRACTION: Two reviewers independently extracted data on study design, setting, population, interventions, comparisons, and detailed information on readmissions. DATA SYNTHESIS: Of the 1363 records reviewed, 26 studies met the inclusion and exclusion criteria. Of these studies, 21 were retrospective, and there was significant variation in the inclusion and exclusion criteria. The pooled estimate of 30-day readmissions was 26%(95% confidence interval [CI], 22%–30%). Few studies examined readmission preventability or the relationship between readmissions and social determinants of health. Reasons for readmission were highly variable. An increased MELD score was associated with readmissions in most studies. Readmission was associated with increased mortality. CONCLUSION: Hospital readmissions frequently occur in patients with cirrhosis and are associated with liver disease severity. The impact of functional and social factors on readmissions is unclear.